Never be nervous again [soundrecording] overcome your fear of public speaking - Sarnoff, Dorothy; Metzner, Jim.; Moore, Gaylen (New York Simon & Schuster, 1992)
Discusses the essential techniques on eliminating nervousness when speaking in public.
Keywords: Public speaking; Oral communication -- Methodology; Personality development; Communication